2013
DOI: 10.5489/cuaj.753
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted laparoscopic partial nephrectomy: Early single Canadian institution experience

Abstract: Background: Although robot-assisted partial nephrectomy (RALPN) has been increasingly adopted, open procedures continue to be the reference nephron-sparing technique. We describe our initial surgical outcomes of RALPN in our single institution robotic program. Methods: Between January 2011 and February 2013, 65 consecutive patients underwent a RALPN by 2 surgeons. Preoperative characteristics, including the R.E.N.A.L. nephrometry score, perioperative parameters, and postoperative course, including renal functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 30 publications
1
11
1
2
Order By: Relevance
“…10 Furthermore, the simultaneous presence of negative margins, minimal decreases in eGFR and no urological complications, defined as the trifecta rate, 11 was achieved in 56.9% of cases. 7 This result seems quite lower than the value (68%) reported by Hung and colleagues. 11 They used a larger cohort of robotic/laparoscopic partial nephrectomies performed at a high-volume centre by a single experienced surgeon.…”
Section: 9contrasting
confidence: 55%
See 1 more Smart Citation
“…10 Furthermore, the simultaneous presence of negative margins, minimal decreases in eGFR and no urological complications, defined as the trifecta rate, 11 was achieved in 56.9% of cases. 7 This result seems quite lower than the value (68%) reported by Hung and colleagues. 11 They used a larger cohort of robotic/laparoscopic partial nephrectomies performed at a high-volume centre by a single experienced surgeon.…”
Section: 9contrasting
confidence: 55%
“…6 Ploussard and colleagues recently reported an interesting single-institution Canadian experience of 65 consecutive RAPNs performed between 2011 and 2013 by 2 surgeons with prior experience in robot-assisted radical prostatectomy or pure laparoscopic partial nephrectomy. 7 The mean tumour size was 3.9 cm and, remarkably, 47.7% of those masses were >4 cm in maximum diameter. The tumour complexity was evaluated by the R.E.N.A.L.…”
mentioning
confidence: 99%
“…10,19 Additionally, we used kidney scintigraphy, 180 days preand postoperatively, to evaluate the function of the operated kidneys. The change in eGFR, 1 year postoperatively, was approximately 10%, which was similar to that in previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Robotic surgery has the advantages of removing tremor, providing surgeons with enhanced capabilities including a three‐dimensional, magnified view, and fulfills the requirements of effective laparoscopic surgery. In the literature, the number of studies including RAPN series has increased in recent years [12–18]. In the early studies, the results of initial experiences were reported; however, now the results of quite extensive series comparing robotic procedure with laparoscopic PN and open surgery are being published.…”
Section: Discussionmentioning
confidence: 99%